Global transcriptional response of oral squamous cell carcinoma cell lines to health-associated oral bacteria - an in vitro study. Issue 1 (31st December 2022) - Baraniya, Divyashri; Chitrala, Kumaraswamy Naidu; Al-Hebshi, Nezar Noor
ABSTRACT: Background: We have recently demonstrated that health-associated oral bacteria Streptococcus mitis, Neisseria flavescens, and Haemophilus parainfluenzae induce cytotoxicity in oral squamous cell carcinoma (OSCC) cell lines and downregulate CD36, a cancer-assocaited gene. Aim: To explore the effect of these three species on global transcriptome of OSCC cell lines. Methods: Gene expression of cell lines CAL27, SCC4 and SCC25 cocultured with the test species was assessed with Clariom-S Human microarray. Porphyromonas gingivalis was included as a pathogenic control. Data were analyzed using Ingenuity Pathway Analysis. Results: The results differed by species and cell line. Overall, the transcriptional changes by S. mitis were predominantly anti-cancer including inhibition of HOTAIR regulatory pathway, JAK/Stat signaling, cyclins/cyclin-dependent kinases, and endothelin1 signaling. H. parainfluenzae and N. flavescens resulted in a mix of pro- and anti-cancer responses including activation of acute phase response, pro-inflammatory interleukins signaling, TREM-1 signaling, and tumor microenvironment pathway; but downregulation of cell cycle by inhibition of cyclins and cyclin-dependent kinases. P. gingivalis had a predominantly pro-cancer effect limited to SCC4, including upregulation of inflammatory pathways, phospholipases and PI3K signaling. Conclusion: These findings provide a new insight into the role of commensal oral bacteria in OSCC. Animal studies are required to further explore them.